2013
DOI: 10.1161/atvbaha.113.301375
|View full text |Cite
|
Sign up to set email alerts
|

Induction of ATF3 Gene Network by Triglyceride-Rich Lipoprotein Lipolysis Products Increases Vascular Apoptosis and Inflammation

Abstract: Objective Elevation of triglyceride-rich lipoproteins (TGRL) contributes to the risk for atherosclerotic cardiovascular disease (ASCVD). Our work has shown that TGRL lipolysis products in high physiological to pathophysiological concentrations cause endothelial cell injury; however, the mechanisms remain to be delineated. Approach and Results We analyzed the transcriptional signaling networks in arterial endothelial cells exposed to TGRL lipolysis products. When human aortic endothelial cells (HAEC) in cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 41 publications
8
56
2
2
Order By: Relevance
“…Our previous studies indicated acute exposure to hydrolyzed TGRLs (TGRL lipolysis products) lead to inflammatory injury in human aortic endothelial cells (22,23,27,28), and we hypothesized similar effects may occur in the vasculature of the brain. In our in vitro model of cultured HBMECs, TEM revealed ultrastructural abnormalities in response to TGRL lipolysis products indicative of lipotoxic injury, including mitochondrial swelling and increased levels of lipid droplets in close proximity to mitochondria at 3 h. To further investigate the particular pathway responsible for this injury, we assayed for production of ROS and detected notably elevated levels of superoxide within 15 min of TGRL lipolysis product treatment that were significantly reduced by concomitant treatment with SOD, suggesting that TGRL lipolysis product-mediated HBMEC injury is dependent, at least in part, on elevated ROS.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Our previous studies indicated acute exposure to hydrolyzed TGRLs (TGRL lipolysis products) lead to inflammatory injury in human aortic endothelial cells (22,23,27,28), and we hypothesized similar effects may occur in the vasculature of the brain. In our in vitro model of cultured HBMECs, TEM revealed ultrastructural abnormalities in response to TGRL lipolysis products indicative of lipotoxic injury, including mitochondrial swelling and increased levels of lipid droplets in close proximity to mitochondria at 3 h. To further investigate the particular pathway responsible for this injury, we assayed for production of ROS and detected notably elevated levels of superoxide within 15 min of TGRL lipolysis product treatment that were significantly reduced by concomitant treatment with SOD, suggesting that TGRL lipolysis product-mediated HBMEC injury is dependent, at least in part, on elevated ROS.…”
Section: Discussionmentioning
confidence: 92%
“…by guest, on May 12, 2018 www.jlr.org Downloaded from (22), we investigated the involvement of ATF3 in the brain microvascular endothelial cell responses to TGRL lipolysis products. We observed markedly upregulated ATF3 expression within 3 h of treatment, as well as increased nuclear accumulation of ATF3.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations